1981
DOI: 10.1021/bk-1981-0161.ch008
|View full text |Cite
|
Sign up to set email alerts
|

Experience in the Separation and Purification of Transplutonium Elements in the Transuranium Processing Plant at Oak Ridge National Laboratory

Abstract: 8y acceptance of this articia, th« publishar or racipicnt acknowlcdgas tha U.S. Qovarnmant'i right to ratain a nonaxclutivc, rayalty-fra* licanta in and to any copyright covering tha articia. MASTER Research sponsored by the Office of Basic Energy Sciences, U.S. Department of Energy under contract W-7405-eng-26 with, the Union Carbide Corporation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…• Target dissolver-This Zr tank (T-70) is mounted in the floor of cubicle 7 so that irradiated targets may be placed into the tank via a covered access port in the top of the tank using manipulators. Dissolution processes have been implemented since the late 1960s, employing dissolution in caustic nitrate for removal of Al, followed by acid dissolution of actinide oxides (Burch et al 1970;King et al 1980;Felker 1995).…”
Section: Existing Facilitiesmentioning
confidence: 99%
“…• Target dissolver-This Zr tank (T-70) is mounted in the floor of cubicle 7 so that irradiated targets may be placed into the tank via a covered access port in the top of the tank using manipulators. Dissolution processes have been implemented since the late 1960s, employing dissolution in caustic nitrate for removal of Al, followed by acid dissolution of actinide oxides (Burch et al 1970;King et al 1980;Felker 1995).…”
Section: Existing Facilitiesmentioning
confidence: 99%
“…The order of the purification is as follows. The cation exchange a-HIB column was performed in the traditional fashion, as discussed earlier, to recover a 252 Cf fraction free from 248 Cm and other decay products [7][8][9][10]. After the cation exchange a-HIB column, the 252 Cf material was converted to a chloride salt by taking it to dryness in HCl several times and dissolved in 2.0 M NH 4 SCN -0.1 M CH 2 O 2 (36 mL), and was passed through a TEVA column with a 1.5 cm ID and a 10 mL BV.…”
Section: Eichrom Ln Resin Hcl Systemmentioning
confidence: 99%
“…This study concluded that the facility is classified in the 'Low" hazard category. The contained calutrons and associated support and laboratory areas are described in the 1…”
Section: Function: Separation Of Transuranium Elementsmentioning
confidence: 99%